Development of Comics Learning Media for Buying and Selling Practices on Social Arithmetic - Husnuz Zaimah (Southeast Asian Mathematics Education Journal, 2020)
This study was conducted to develop comic learning media which was valid, practical, and effective to help students understand the concept of social arithmetic.  This study is a  developmental study which adapts the stages of Borg and Gall. The stages are 1) initial study and gathering information,(2) planning, (3) developing the initial product, (4) limited field trial, (5) revising the initial product, (6) field trials, and (7) revision of the final product. The result of this study was a comic learning media for buying and selling practices on social arithmetic which has met the valid, practical, and effective criteria. Based on the validity results involving media and educational experts showed that this comic learning media was valid,  with the percentage of validity respectively  93.6%  (very feasible)  and  96%  (very feasible). Based on the implementation of this media to VII grade students of MTs N (junior high school)  2  Mojokerto,  an assessment by students as the media users showed that this media was practical with the percentage of 82.3% (very good) during the limited field trial, and 92.31% (very good) during field trials. The effectiveness of this media is based on students’ achievement results that 91% of students were in the good and excellent category. It means that this comic learning media is effective.  Based  on  these  results,  it  can  be  concluded that this media was appropriate to be used as a learning medium on the topic of social arithmetic